(untitled) (Western European Journal of Medicine and Medical Science, 2025)
Unfavorable working conditions determine physiological changes in the body of workers at a plant producing reinforced concrete structures, tension in thermoregulatory processes, and the cardiovascular system, which is determined by the influence of harmful production factors on the functional state of the whole organism during the working day.